PENINGKATAN HASIL BELAJAR MATA KULIAH KONSEP SENI MAHASISWA PGSD-FKIP UNIVERSITAS RIAU (UR) MELALUI PENERAPAN PENDEKATAN PEMBELAJARAN MULTIKULTURAL - Antosa, Zariul; N, Lazim.; Gunawan, Indra (ATTA`DIB, 2016)
One of the factors that influence students' poor results in the subject of the concept of art is the difficulty in understanding the learning content. Students do not understand the background of art and understanding of art. It is necessary for improvement of the learning process. In this study, the improvement of learning the concept art courses will be conducted through quasi experimental study with implementing multicultural learning approach. The learning approach is capable of making students construct their own knowledge, increasing student activity, can improve self-reliance, thinking in a systematic, logical and careful to formulate learning outcomes compatible with the objectives. The study was conducted specifically on the background of the art materials, understanding, functions and types of art. The main objective of this study is to analyze the learning outcome art concept between students who received study with the application of multicultural approach with students who acquire learning in general. The results indicate that there are differences in the average value of the initial test and final test, but not statistically significant difference to the learning outcome art concept between students who obtain application of learning through multicultural approach with students who acquire such learning in general.